Kahoot! As A Digital Quiz in Learning English: Graduate Students’ Perspectives - Pajrian Noor (English Education:Journal of English Teaching and Research, 2023)
The use of technology in learning English is very important, it can make the process of learning more effective and easy. Here, the kahoot! is one of the digital quiz in learning English, that used online media very process of learning. The purpose of this study is to know the perspective of graduate students’ of English education study about the uses of kahoot! as a digital quiz in learning English. This study used questioners to collects data. The number of the participants involved in this study were 10 students from private university in Yogyakarta that sitting in the second master program. In addition the methodology in this study is descriptive qualitative. This study found that Kahoot! makes the atmosphere of classroom more interactive and energetic, the participant were more interested and motivated. In addition Kahoot! gives the positive influenced in learning process and make the classroom more interactive fun.